THE INNOVATIVE METHOD OF HEAT TREATMENT OF LIQUID FOOD MEDIA - I. A. Kuznetsova; A. V. Kuznetsov; L. A. Kistanova (Современная наука и инновации, 2022)
A method of inactivation of the microflora of the "waste" brine after salting cheese using a cavitation heat generator is substantiated and proposed.